Carbachol excites sublaterodorsal nucleus neurons projecting to the spinal cord. (16th January 2014) - Weng, F. J.; Williams, R. H.; Hawryluk, J. M.; Lu, J.; Scammell, T. E.; Saper, C. B.; Arrigoni, E.
Abstract : Key points: Activation of spinally projecting sublaterodorsal nucleus (SLD) neurons inhibits motor activity, in part through spinal inhibitory interneurons, to produce muscle atonia during rapid‐eye‐movement (REM) sleep. It has long been hypothesized that acetylcholine released during REM sleep contributes to REM sleep atonia through activation of SLD neurons. We show, using whole‐cell recordings in brainstem slices, that acetylcholine directly excites spinally projecting SLD neurons via M1 and M3 muscarinic receptors, and increases afferent excitatory synaptic input to these neurons. These results suggest that acetylcholine contributes to REM sleep muscle atonia through excitation of spinally projecting SLD neurons. Abstract: Considerable electrophysiological and pharmacological evidence has long suggested an important role for acetylcholine in the regulation of rapid‐eye‐movement (REM) sleep. For example, injection of the cholinergic agonist carbachol into the dorsomedial pons produces an REM sleep‐like state with muscle atonia and cortical activation, both of which are cardinal features of REM sleep. Located within this region of the pons is the sublaterodorsal nucleus (SLD), a structure thought to be both necessary and sufficient for generating REM sleep muscle atonia. Subsets of glutamatergic SLD neurons potently contribute to motor inhibition during REM sleep through descending projections to motor‐related glycinergic/GABAergic neurons in the spinal cord and ventromedial medulla. Prior electrophysiological and pharmacological studies examining the effects of acetylcholine on SLD neurons have, however, produced conflicting results. In the present study, we sought to clarify how acetylcholine influences the activity of spinally projecting SLD (SLDsp) neurons. We used retrograde tracing in combination with patch‐clamp recordings and recorded pre‐ and postsynaptic effects of carbachol on SLDsp neurons. Carbachol acted presynaptically by increasing the frequency of glutamatergic miniature excitatory postsynaptic currents. We also found that carbachol directly excited SLDsp neurons by activating an Na + –Ca 2+ exchanger. Both pre‐ and postsynaptic effects were mediated by co‐activation of M1 and M3 muscarinic receptors. These observations suggest that acetylcholine produces synergistic, excitatory pre‐ and postsynaptic responses on SLDsp neurons that, in turn, probably serve to promote muscle atonia during REM sleep.